INFLUENCE OF CYCLOFERON ON THE CELLULAR SUSCEPTIBILITY TO INTERFERON-α2 IN VITRO IN PATIENTS WITH INFECTIOUS MONONUCLEOSIS CAUSED BY EPSTEIN– BARR VIRUS - L. M. Kurtasova; N. A. Shakina; A. R. Smidt; L. A. Ikkes (Медицинская иммунология, 2018)
Our aim was to study the effect of cycloferon on in vitro susceptibility of peripheral blood leukocytes to interferon-α2 in children with infectious mononucleosis in acute phase caused by Epstein-Barr virus (EBV). Materials and methods were as follows: the study included 23 children 4 to 6 years of age admitted in acute period of infectious mononucleosis. The control group consisted of 15 healthy children of the same age group. In vitro susceptibility of peripheral blood leukocytes to interferon-α2 was determined by the method of L.M. Kurtasova (2007).Four types of in vitro response of peripheral blood leukocytes to interferon-α2 upon induction by cycloferon have been revealed in both healthy children and patients with EBV-positive infectious mononucleosis. Differences in occurrence rates of these 4 types of reactions have been found among patients with EBVinfection, in comparison with the group of healthy children. There was no regular dose-dependent changes in susceptibility of peripheral blood  leukocytes to interferon-α2 in vitro after cycloferon induction in the group of children with EBV-infection. depending on the dose, which have been revealed in healthy children.